Anthraquinone extraction from Morinda sp. root powder under steam pressurized conditions - Taweyot Kunyotying (2018)
Three types of containers and six strategies to control the evaporation of 80%v/v ethanol for extraction of anthraquinone from dried Morinda sp. root powder in a pressurized steamer at 20 psi for 30 min were investigated. These were the most extreme conditions possible in the system investigated. A tightly sealed 231 ml jam jar with a metal screw cap (diameter 5.4 cm, height 10.1 cm) was chosen as the most appropriate container with the ability to withhold 65.0 ± 5.6% of the original liquid volume after pressurization with saturated steam. The optimal pressure level and time for pressurized anthraquinone extraction in the jar containing 80%v/v ethanol was 5 psi for 5 min with the corresponding level of extracted anthraquinone being 30.9 ± 0.5 mg/g dried root powder, with a minimal extraction cost of merely 2.65 ± 0.04 baht/mg. Further experiments on the effect of varying the ethanol concentration revealed that 65%v/v ethanol achieved the highest extracted anthraquinone level of 38.4 ± 0.7 mg/g with a corresponding extraction cost of only 2.01 ± 0.04 baht/mg. The problem of reproducibility and the existence of outliers encountered previously with pressurized steam extraction were resolved and eliminated with the use of the 231 ml jam jar.